THE ROLE AND DEVELOPMENTAL TRENDS OF THE PRELIMINARY INVESTIGATION INSTITUTION IN CRIMINAL PROCEDURAL LAW - Xasanov Boburbek Utkir o’gli; Boburbek Khasanov Utkir ugli (International Journal of Business, Law and Political Science, 2025)
Objective: This study investigates the theoretical foundations, legislative developments, and procedural tools that shape the preliminary investigation phase under Uzbekistan’s Criminal Procedure Code, aiming to evaluate its effectiveness, legality, and alignment with international standards. Method: A qualitative legal analysis was conducted through a review of statutory provisions, comparative legal practices, and doctrinal literature, supported by examination of recent reforms and practical challenges in investigative procedures. Results: The findings indicate that clear jurisdictional rules enhance specialization and case efficiency, while mechanisms for suspension and resumption of investigations uphold procedural continuity. However, the three-month investigation timeframe is often inadequate, and limitations persist regarding investigator independence and legality of investigative actions. Increased public participation and strengthened prosecutorial oversight are identified as essential for ensuring transparency and legal protection. Novelty: This research provides a comprehensive evaluation of preliminary investigation mechanisms in Uzbekistan, highlighting both structural weaknesses and progressive reforms. It offers novel insights into optimizing procedural guarantees and proposes practical solutions such as enhanced training, international cooperation for extradition, and institutional accountability to uphold human rights and legal certainty in criminal justice.